BOVINE COLLAGEN EFFECT IN MAINTAINING BLOOD SUGAR AND BODY WEIGHT STABILITY IN DIABETIC RATS - Sadikin, Santi; Juliastuti, Henny; Putu Yuni Paryati, Sayu (Fakultas Kedokteran Gigi Unjani, 2025)
Diabetes causes degenerative processes to occur earlier, for example during hyperglycemia with increased levels of Advanced Glycation End Products (AGEs) damaging the body's metabolism. Consuming anti-diabetic medications lowers blood sugar levels; however, hypoglycemia, which can be life-threatening, often occurs. Additionally, patients with diabetic experience uncontrolled weight loss or weight gain. This study aims to test the potential of bovine collagen in maintaining stable blood sugar levels and body weight in rats induced with diabetic. A total of 24 seven-month-old Wistar rats were divided into four groups: negative control group; positive control group induced with streptozotocin at 50 mg/kg body weight (BW) and given water as placebo; a group induced with streptozotocin at 50 mg/kg BW and treated with bovine collagen at a dose of 2x 400 mg/kg BW/day; and a third group of healthy rats receiving bovine collagen at the same dosage. All groups were treated for four weeks, during which body weight and blood sugar levels were monitored. The results indicated that diabetic rats treated with bovine collagen had better weight control compared to the positive control group in the first week (p = 0.033); however, in subsequent weeks, bovine collagen did not affect body weight. Blood sugar levels in the four groups of rats during the first, second, and third weeks showed that bovine collagen significantly reduced blood sugar levels in diabetic rats from the first to the third week (p < 0.05). It is possible that additional doses or the administration of antioxidant flavonoids may be necessary from the second week onward to maintain weight stability. DOI : 10.54052/jhds.v4n3.p325-338